Molecular study of the “Escoba Blanca” variety of Sesamum indicum L. used in Paraguay - Martínez-López, Roberto; Esfrain Pereira, Walter; Arrua, Andrea; Fernández , Danilo; Centurión, Liz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The high quality of sesame seeds originating in the country has led Paraguay to be among the main exporters. Of the varieties available in Paraguayan territory, the most widespread is ‘‘Escoba Blanca’’, which, possibly due to the multiplication process, could promote changes in its allele frequency, diversity, and genetic purity. This work was carried out, aiming to determine the genetic differentiation between 50 populations/seedbeds/banks from seven Paraguayan companies collecting ‘‘Escoba Blanca’’ sesame, using microsatellite markers. These seven banks/companies/cooperatives collect and represent samples from all the producers/seedbeds located in different departments of the Eastern and Western Region (Chaco) of the country, with whom they work, market, and collect sesame. Plant tissue was obtained to extract DNA, from seedlings planted especially for the purpose, using all the included samples/accessions. Six microsatellite markers were used: GBssrsa184, GBssrsa123, GBssrsa182, GBssrsa108, GBssrsa08, and GBssrsa72. The following were calculated: number and frequency of alleles, distance/groupings, differentiation between populations, and their genetic structure. The mean number of alleles per locus ranged from 1.33 to 3.00. In the markers, GBssrsa184 and GBssrsa108, three populations presented a higher frequency of alleles. The populations examined exhibited a wide degree of genetic differentiation between them, with the identification of four groups, with greater and less purity respectively.